2010
DOI: 10.1002/lary.20800
|View full text |Cite
|
Sign up to set email alerts
|

The management of thyroid carcinoma invading the larynx or trachea

Abstract: Long-term (>10-20 years) prospective studies are required to compare the outcome after shave excision with segmental airway resection for thyroid carcinoma. Based on the current literature and on our experience, we advocate circumferential tracheal resection in the setting of airway involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
97
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(99 citation statements)
references
References 56 publications
(108 reference statements)
0
97
0
2
Order By: Relevance
“…they suggested that the upper respiratory tract should be sacrificed only if the tumor cannot be excised macroscopically. Gaissert et al [4][5][6] analyzed patients with thyroid carcinoma of different malignity grade and selectively performed radical tumorectomy in the patients with tracheal invasion. the postsurgical follow-up showed that 50 % of them survived for 20 years with good quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…they suggested that the upper respiratory tract should be sacrificed only if the tumor cannot be excised macroscopically. Gaissert et al [4][5][6] analyzed patients with thyroid carcinoma of different malignity grade and selectively performed radical tumorectomy in the patients with tracheal invasion. the postsurgical follow-up showed that 50 % of them survived for 20 years with good quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…The patients show symptoms according to the grade of their clinical invasion, although patients with intra-luminary invasions generally show dyspnea and hemoptysis. [12] Most of the cases with tracheal invasion represent superficial tracheal involvement and are first diagnosed during thyroidectomy. [13] Surgeons have to decide whether to perform a radical resection, including the trachea and/or larynx, or to perform limited resection with I131 or radiotherapy to ablate the residual disease.…”
Section: Discussionmentioning
confidence: 99%
“…The suggestion made in this report was that shave resection is incomplete, and a high rate of local failure must be expected. [12] Nishida et al [21] saw no indication for tracheal resection in those carcinomas that abutted the external perichondrium and performed a shave resection. Similarly, in this study, patients who had early stage (stage I according to Shin classification) laryngotracheal invasion did not show recurrence after shaving.…”
Section: Discussionmentioning
confidence: 99%
“…In this situation, determining the exact extent of invasion requires histopathological assessment that can only be achieved postoperatively. Therefore, some authors recommend a full-thickness excision including the mucosa of the airway (9,20,(33)(34)(35)(36)(37). This approach ensures a histologically negative margin but results in increased surgical complexity and significant functional impairment.…”
Section: Invasion Of the Airwaymentioning
confidence: 99%